(untitled) (Journal of human and social sciences, 2022)
The study aimed to identify the attitudes of secondary school students towards technical education. The study adopted descriptive analytical approach for the selected sample (640) students. The results showed that students’ attitudes towards technical education is medium and tends to be declined. The results confirmed that there were no statistically significant differences between students’ attitudes in terms of their gender. Parents’ levels of income and education proved to have no effect. Family technical experience proved to have no effect as well. The paper concluded with some recommendations such as: raising parents and students’ awareness towards technical education. Limitations and shortcomings were acknowledged at the end of the paper